The relationship between amino acids and gastroesophageal reflux disease: evidence from a mendelian randomization analysis combined with a meta-analysis - Shen, Jianjun; Guo, Yongqing; Cao, Rui (Frontiers in Immunology, 2025)
BackgroundGastroesophageal Reflux Disease (GERD), a prevalent gastrointestinal disorder globally, exhibits variable prevalence across regions, with higher frequencies observed in Western nations and lower in Asian countries. Key contributing factors encompass unhealthy eating patterns, tobacco use, consumption of alcohol, excess weight, and obesity, along with health conditions such as gestation and diabetes. Common manifestations include heartburn and a burning discomfort behind the breastbone, which, without appropriate management, can progress to more severe issues like esophagitis and Barrett’s esophagus. Approaches to management and prevention primarily involve modifications in lifestyle, pharmacotherapy, and surgical interventions when deemed necessary. Utilizing Omics Mendelian Randomization (OMR) to investigate the causative links between genetic variants and diseases provides insights into the biological underpinnings of gastroesophageal reflux diseasec. It aids in pinpointing novel targets for therapy. The influence of amino acids in gastroesophageal reflux disease demonstrates the complexity, having the potential to both mitigate and intensify symptoms, underscoring the significance of personalized nutrition and therapeutic strategies.MethodsThis study is based on the omics mendelian randomization method, coupled with meta-analysis techniques, to enhance the precision of the research findings. Furthermore, a reverse validation procedure was implemented to validate the association between the positive findings and disease outcomes further. Throughout the study, multiple correction measures were employed to ensure the accuracy and reliability of the results.ResultsBased on our research methodology, we have ultimately discovered that glutamate exacerbates gastroesophageal reflux disease, increasing its risk. The data supporting this includes analysis of 20 amino acids and outcomes from the Finnish database, which showed that glutamate had an odds ratio (OR) for gastroesophageal reflux disease risk of 1.175(95% confidence interval (CI): 1.000 ~ 1.380, P = 0.05), and a beta value of 0.161. Analysis with outcomes from the UK database indicated that glutamate had an OR for gastroesophageal reflux disease risk of 1.399(95% CI: 1.060 ~ 1.847, P = 0.018) and a beta value of 0.336. After conducting a meta-analysis of the MR results and applying multiple corrections, the combined OR of glutamate for gastroesophageal reflux disease risk was 1.227 (95% CI: 1.068 ~ 1.411 P = 0.043); the beta values of the three primary MR outcomes were consistent in direction. Building on the positive results, reverse validation with outcome data from two different database sources for glutamate showed: in the Finngen database, with gastroesophageal reflux disease as the exposure, the Inverse Variance Weighted (IVW) method resulted in a P-value of 0.059; in the IEU database under the same condition, the IVW P-value was 1.433.ConclusionsGlutamate may increase the risk and exacerbate the progression of gastroesophageal reflux disease through mechanisms such as impacting the nervous system and promoting inflammatory responses. Delving into the role of glutamate in gastroesophageal reflux disease enriches our understanding of the disease’s biological mechanisms and may offer new strategies for clinical treatment and nutritional management. This insight can aid in developing healthier dietary plans, thereby benefiting patients.